PENERAPAN NUTRITION CARE PROCESS (NCP) PADA PENDERITA HIPERKOLESTEROLEMIA KOMPLIKASI HIPERTENSI RAWAT INAPDI BLU RSUP PROF.DR.R.D KANDOU MANADO - Irza N. Ranti; Rivolta G.M. Walalangi (Jurnal GIZIDO, 2014)
Hypercholesterolemia is one type of blood lipid profile abnormalities (dyslipidemia), whichis marked by high levels of low-density lipoprotein cholesterol (LDL) and triglyceride levelsand cholesterol levels of High Density Lipoprotein (HDL) is low. Hipertensia dalah a stateof blood pressure ≥ 140/90 mmHg, the disease is not contagious but can cause death.This study aims to determine the application of the Nutrition Care Process (NCP) inhypercholesterolemic patients with hypertension complication of hospitalization in thedepartment of Prof. BLU Dr. R.D Kandou Manado.This research is a descriptive study design used is a case study, the number of samples 1person who meets the inclusion criteria. This research was carried out for 2 weeks in June2014, housed diruangan Prof Dr Irina C BLU Dr R. D. Kandou Manado. Assessment NCPstages namely nutrition assessment, nutrition diagnosis, and monitoring and evaluation ofnutrition intervention processed and analyzed descriptively.The results were obtained prior to the study showed patients cholesterol levels were highat 280 mg / dl and high blood pressure is 160/120 mm Hg. Nenergi asupa level, proteins,fats and carbohydrates are severe deficit (<70%) and nutritional status of the patient isobese (BMI 27.34 kg / m2). After a study of total cholesterol to 219 mg / dl (mediumcontrol criteria), and blood pressure of 120/80 mmHg be (normal). To the level of energyintake be 70.28% (moderate deficit), 72.85% protein (moderate deficit), fat 70.37%(moderate deficit), carbohydrates 67.01% (defisitberat) and decreased by 1 kg of bodyweight and nutritional status of the patient is overweight (26.95 kg / m2). Conclusiondecrease total cholesterol and blood pressure checks, as well as increased energy andnutrient intake of the patients but has not reached the tiers supan good.